The Effect of Dividend Policy and Debt Policy on Firm Value: Empirical Evidence from LQ45 Companies Listed on the Indonesia Stock Exchange (2021–2023) - Bambang Wahyudi; Feri Tristiawan; Wahyu Adi Wibowo (LP2M Politeknik Jambi, 2026)
This study aims to examine the effect of dividend policy and debt policy on firm value in LQ45 companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Firm value is an important indicator reflecting investors’ perceptions of a company’s performance and future prospects. Dividend policy was proxied by the Dividend Payout Ratio (DPR), debt policy was proxied by the Debt to Equity Ratio (DER), while firm value was measured using the Price to Book Value (PBV). This study employed a quantitative approach using secondary data obtained from the annual financial statements of LQ45 companies listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling, resulting in 28 companies with a total of 84 observations during the research period. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0.9.9 software. The results indicate that dividend policy has a positive and significant effect on firm value. In addition, debt policy also has a positive and significant effect on firm value. These findings support signaling theory, which explains that dividend distribution and the optimal use of debt can provide positive signals to investors regarding the company’s future prospects. Furthermore, the findings support trade-off theory, which states that optimal debt utilization can increase firm value through tax benefits (tax shield). This study contributes to the development of financial management literature and provides insights for investors and company management in making financial decisions to maximize firm value.